Presumptive Income Taxation : Administrative, Efficiency, and Equity Aspects - Casanegra de Jantscher, Milka (IMF Working Papers; Working Paper ;, 1987)
This paper discusses assessment of income on the basis of approximate indicators as opposed to conventional records. Such a method of assessment, known as presumptive income taxation, is widely used in many developing and industrial countries; however, it has been neglected in public finance literature. In most cases the presumptive approach has been followed for administrative reasons, but this paper argues that more attention should be paid to the efficiency implications of presumptive taxes.